Generic Model to Send Secure Alerts for Utility Companies - I. Galván-Bobadilla (Ingeniería. Investigación y Tecnología, 2010)
In some industries such as logistics services, bank services, and others, the use of automated systems that deliver critical business information anytime and anywhere play an important role in the decision making process. This paper introduces a "Generic model to send secure alerts and notifications", which operates as a middleware between enterprise data sources and its mobile users. This model uses Short Message Service (SMS) as its main mobile messaging technology, however is open to use new types of messaging technologies. Our model is interoperable with existing information systems, it can store any kind of information about alerts or notifications at different levels of granularity, it offers different types of notifications (as an alert when critical business problems occur, as a notification in a periodical basis or as 2 way query). Notification rules can be customized by final users according to their preferences. The model provides a security framework in the cases where information requires confidentiality, it is extensible to existing andnew messaging technologies (like e-mail, MMS, etc). It is a platform, mobile operator and hardware independent. Currently, our solution is being used at the Comisión Federal de Electricidad (Mexico´s utility company) to deliver secure alerts related to critical events registered in the main power generation plants of our country.